Efektivitas Komunikasi Nonverbal Supeltas dalam Mengatur Lalu-lintas di Surakarta - Sukarno, Bedjo (Universitas Ahmad Dahlan, 2015)
Traffic control volunteer worker motivation objective indirectly want to create traffic road conditions are not always jammed, but they were able to unravel for smooth for all road users with communication devices owned that body language and whistles. Nonverbal messages such as body language, which refers to an object used consistently by its users. Appearance and style of volunteers who served in front of the highway users make sense of something that is consistent because it pollutes the material that has been prevailing in the society. Thats when the process of formation of meaning in the minds of the road users in general.Keywords: Volunteer Officers Motive, Credibility Evective Volunteer Officers and nonverbal messages.